2020
DOI: 10.3390/catal10080851
|View full text |Cite
|
Sign up to set email alerts
|

Newly Isolated Alkane Hydroxylase and Lipase Producing Geobacillus and Anoxybacillus Species Involved in Crude Oil Degradation

Abstract: Isolation and studies of novel, crude oil biodegrading thermophilic strains may provide a wider knowledge in understanding their role in petroleum degradation. In this study, the screening of ten new thermophilic strains revealed that all strains were alkane hydroxylase producers and seven of them produced lipase concurrently. Three best strains were characterized and identified through 16S rRNA sequence analysis as Geobacillus sp. D4, Geobacillus sp. D7, and Anoxybacillus geothermalis D9 with GenBank accessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, only a few studies have assessed the potential of members of Anoxybacillus for use in this field. For example, A. geothermalis is able to degrade crude oil while producing alkane hydroxylase and lipase ( Yusoff et al, 2020 ); and Anoxybacillus sp. WJ-4, a new thermophilic strain isolated in the Daqing oilfield, is capable of utilizing alkanes (C8–C22) as a sole source of carbon for growth and produced an oligosaccharide–lipid–peptide bioemulsifier with an EI% over 60%, with increased cell-surface lipophilicity to 65% during hydrocarbon degradation ( Xia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have assessed the potential of members of Anoxybacillus for use in this field. For example, A. geothermalis is able to degrade crude oil while producing alkane hydroxylase and lipase ( Yusoff et al, 2020 ); and Anoxybacillus sp. WJ-4, a new thermophilic strain isolated in the Daqing oilfield, is capable of utilizing alkanes (C8–C22) as a sole source of carbon for growth and produced an oligosaccharide–lipid–peptide bioemulsifier with an EI% over 60%, with increased cell-surface lipophilicity to 65% during hydrocarbon degradation ( Xia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the identified bacteria belonged to the genera Geobacillus and Parageobacillus. Strain D9 was identified previously as Anoxybacillus geothermalis D9 (MK615936.1) (Yusoff et al, 2020). The isolation and identification of these strains at 70 • C suggest a possible role of these microorganisms to degrade crude oil in a high-temperature environment.…”
Section: Discussionmentioning
confidence: 84%
“…The break down of hydrocarbons into simpler molecules allow their assimilation and further degradation within the cell by intracellular enzymes, thus increasing degradation efficiency due to less hydrocarbon being present in the medium (Wasoh et al, 2019). A recent study by Yusoff et al (2020) found that strain D9 exhibited extracellular alkane hydroxylase activity on the first day, but the activity reduced following the increase of the intracellular alkane hydroxylase activity. Further increase in biodegradation efficiency after the enzyme activity declined could also be due to the higher (more than 80%) removal of long-chain n-alkane (C 18 to C 37 ), especially by strains N3A7, MK7, DFY1, AD11, and AD24 on the 3 rd day of incubation.…”
Section: Discussionmentioning
confidence: 95%
“…This could be due to the presence of hydrocarbon degrading enzymes such as laccases, manganese peroxidases lignin peroxidases and lipase. Yusoff et al (2020) reported that lipase is involved in inducing the lipolytic reactions of emulsified hydrocarbonat the lipid-water interface, thus assisting the hydrocarbon uptake and showed showed the presence of lipase intracellularly or extracellularly produced by hydrocarbon degraders Joutey et al (2014) reported that fungi are effective, especially when it comes to breaking down natural polymeric materials, because they have extracellular multi-enzyme complexes. They can also colonize and penetrate substrates quickly, because of their hyphal networks, they can transfer and redistribute nutrients throughout their mycelium.…”
Section: Discussionmentioning
confidence: 99%